POST-TRAUMATIC STRESS DISORDER REFLECTED IN THE CHARACTER OF CHERRY IN ANTHONY RUSSOâ€™S CHERRY (2021) - Krisdayana Kiyat Fietama; Ana Widiyanti (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2023)
This study is aimed to analyze: (1) the PTSD of the main character presented in Anthony Russoâ€™s â€œCherryâ€, (2) the effect of PTSD toward the main character's life reflected in Anthony Russo's â€œCherryâ€. The study uses descriptive qualitative method to analyze the film. The collecting data of the research method includes watching and reading, identifying, classifying, and selecting. The analyzing data of the research method by used displaying, explaining, and interpreting. The result of the study: (1) the PTSD of the main character presented in Anthony Russoâ€™s â€œCherryâ€ such as experiencing and witnessing a past event that was unpleasant and frightening and appeared accompanied by symptoms such as re-traumatic and hyperarousal; (2) the effects of PTSD toward the main character's life in the form of effect on mental health, effect on physical health, and effect on quality of life.